Characteristics of Rural Crack and Powder Cocaine Users: Gender and Other Correlates - Pope, Sandra K. (2011)
BACKGROUND: Little is known about the relationship of gender with cocaine use in rural areas. This study describes these relationships among stimulant users residing in rural areas of Arkansas, Kentucky and Ohio. OBJECTIVES: Understanding characteristics of crack and powder cocaine users in rural areas may help inform prevention, education and treatment efforts to address rural stimulant use. METHODS: Participants were 690 stimulant users, including 274 (38.6%) females, residing in 9 rural counties. Cocaine use was measured by self-report of cocaine use, frequency of use, age of first use, and cocaine abuse/dependence. Powder cocaine use was reported by 49% of this sample of stimulant users and 59% reported using crack cocaine. FINDINGS: Differing use patterns emerged for female and male cocaine users in this rural sample; females began using alcohol, marijuana, and cocaine at later ages than males but there were no gender differences in current powder cocaine use. Females reported more frequent use of crack cocaine and more cocaine abuse/dependence than males, and in regression analyses, female crack cocaine users had 1.8 times greater odds of reporting frequent crack use than male crack users. CONCLUSIONS AND SCIENTIFIC SIGNIFICANCE: These findings suggest differing profiles and patterns of cocaine use for male and female users in rural areas, supporting previous findings in urban areas of gender-based vulnerability to negative consequences of cocaine use. Further research on cocain use in rural areas can provide insights into gender differences that can inform development and refinement of effective interventions in rural communities.